Study about the effects of rehabilitation on quality of life in multiple sclerosis patients - Sangelaji, bahram; Hatamizadeh, nikta; Rashvand, farnoosh; Kazemnejad, Anoshirvan (Advances in Nursing & Midwifery, 2011)
Abstract Background and aim Multiple sclerosis is a progressive demyelization disease which can progress to physical disability in many patients. People with multiple sclerosis face many problems and complications which require appropriate education and interventions. Multidisciplinary neurorehabilitation is an effective treatment for quality of life improvement in MS patents. The purpose of this study is to examine the effect of Hayate noo center rehabilitation protocol on quality of life of MS patents. Materials and methods In this clinical trial 130 MS patients (65 patients as treatment group and 65 as control group) were studied. Participants were randomly selected from patients attending Iran MS society in Tehran. The two groups were matched in terms of sex, age, education, type of MS , marital status , time of onset of MS, and disability status. A questionnaire was used for data collection . The questionnaire consisted of three parts .Part one is demographics information and the 2end part consisted of Persian version of MSQOL-54 questionnaire . This questionnaire has been translated and validated in previous studies , with an 0.96 coefficient (alpha cronbach) reliability . The 3rd part included Persian version of PDDS questionnaire .This test is designed to measure the disability status and has a correlation coefficient of 0.80( spearman correlation) with EDSS(expanded disability status scale).Patients in treatment group participated in the multidisciplinary rehabilitation protocol. This protocol was designed in Hayate noo center. Each patient in treatment group attended in at least 8 sessions of Hayate noo multidisciplinary neurorehabilitation protocol for 3 months. All participants were assessed in terms of their disability status prior to the study. Participants in both groups completed MSQOL-54 before and after the study . The data were analyzed using SPSS software, version 16. Student t-test was used to compare means and Pearson correlation coefficient was used for measuring the correlations. Findings Changes in Quality of life scores in treatment group were statistically significant (p<005). Scores of all subscales in Quality of life measure (except for cognitive domain) increased in treatment group compared with the control group. Physical health composite score increased 8.04 point and mental health composite score improved 7.7 point (P<0.001). Also the social activity of treatment group increased comparing with the control group. Conclusion Use of Hayateno center protocol has increased quality of life scores in MS patients. This improvement is comparable with another center in the world. Keywords: Multiple Sclerosis, Multidisciplinary rehabilitation, quality of life